LCMS Missionaries and an Alien Indian Culture: A Gospel-Culture Engagement at the Margins of Indian Society - Stanish Stanley (Missio Apostolica, 2014)
Does the Gospel message have within it the inherent potential to engage and transform a culture that seems to be alien and at odds with its worldview? A look into the early twentieth century history of the evangelizing efforts of LCMS missionaries in South India provides a glimpse into how the missionaries as the ‘bearers of the Gospel” encountered a native culture at odds with the Biblical message and vision. Through this mission story, the essay argues that Gospel-Culture engagement entails negotiations of varying concerns and aspirations of both the missionary and the “converting” people, with the Gospel enabling the native people to challenge and transform their culture by contextualizing its Biblical promise and hop